Perceptions and Practices of Diabetes Educators in Providing Oral Health Care: A Qualitative Study. Issue 5 (October 2018) - Poudel, Prakash; Griffiths, Rhonda; Wong, Vincent W.; Arora, Amit; Flack, Jeff R.; Khoo, Chee L.; George, Ajesh
Purpose: The purpose of this study was to explore the current perceptions and practices of diabetes educators (DEs) in providing oral health care to people with diabetes. Methods: A qualitative study design involving focus groups was used to gather data. Purposive sampling was used to recruit DEs working across 3 metropolitan hospitals in South Western Sydney, Australia. Results: Fourteen DEs participated in 3 focus groups. Participants had a mean ± SD age of 44.4 ± 9.2 years and 5.2 ± 5.3 years of work experience in diabetes care. Four main themes were identified: perceptions about oral health care and diabetes current oral health care practices, perceptions on incorporating oral health, and suggested model of care. DEs agreed that promoting oral health in diabetes clinics is important, and they reported seeing patients frequently with oral health problems. However, the majority do not include oral health care in consultations, primarily because they have limited knowledge in this area and have not received any formal oral health education or training. Additional barriers were the lack of referral pathways and resources for patient education. DEs were receptive to incorporating oral health provided that the current barriers were addressed. DEs also suggested a multidisciplinary team care approach to promote oral health. Conclusions: Current practices of DEs in oral health care are limited, but they are willing to address oral health. A suggested model of oral health care should include capacity building of diabetes care providers, appropriate dental referral pathways, and a team approach within multidisciplinary diabetes care.